If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -60 = 3x + -14 Reorder the terms: -60 + 5x = 3x + -14 Reorder the terms: -60 + 5x = -14 + 3x Solving -60 + 5x = -14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -60 + 5x + -3x = -14 + 3x + -3x Combine like terms: 5x + -3x = 2x -60 + 2x = -14 + 3x + -3x Combine like terms: 3x + -3x = 0 -60 + 2x = -14 + 0 -60 + 2x = -14 Add '60' to each side of the equation. -60 + 60 + 2x = -14 + 60 Combine like terms: -60 + 60 = 0 0 + 2x = -14 + 60 2x = -14 + 60 Combine like terms: -14 + 60 = 46 2x = 46 Divide each side by '2'. x = 23 Simplifying x = 23
| -6k+4k=10 | | 9(2r-3)-1=5r | | X*5-66=x*3-14 | | (4w^6)/(24w^2) | | 5.9x-2.5-6.9x=1x-2.5 | | 10+7x=4x-23 | | v-8.2=3.62 | | 5x+6=7x-16 | | 30=7x+6 | | 169.92/t=48 | | -10=-6a-4a | | (X^2/2)-(5/6)=12 | | 2n^2-7n=-1 | | 6x-2=78-4x | | 5+55x=44x+8 | | 7x+15=20x-50 | | X^2/2-5/6=12 | | 4(5x-3)+5(3x-1)= | | lne^12=x | | 2x+1=45+6x | | 2x^2-3x+9=8x-3 | | 5x+20=3x+42 | | -2(x+5)+4=3(x+3)+3 | | 12=5n+n | | 25-w=5w | | 3(k+8)+6=15 | | 6x+2=-3+7x | | x+1-(-x)=x | | 3/-5b-1/10=7/20-7/10b | | -10=-(m+6) | | 2k^2-50=0 | | (7x-7)(x+5)= |